Tubing Strength Evaluation and Failure Assessment for Reactivation of Well PDD-2 as Steam Injector Well - Steven Chandra; Wijoyo Niti Daton; Mohammad Hafidz Setiawan (Scientific Contributions Oil and Gas, 2021)
Many old oil wells still exist in Indonesia, some of those wells has been shut in due to several reasons, two of those reasons are: the oil production that declines significantly and weak well integrity so that the well cannot withstand obstructions that occur during production. To maintain and boost Indonesia's oil production, Enhanced Oil Recovery (EOR) methods can be applied in mature fields. One of EOR methods that has the most extensive application is steam flooding, in which the fluid is injected continuously to drive the oil from injector to producer. This EOR method is a successful method to increase heavy-oil production.The application of steam flooding, most notably in older wells presents itself with possible well integrity problem. Steam flooding well has a very high risk of casing and tubing failure that caused by the loads from burst, collapse, tension, and thermal effect due to the high temperature steam that can decrease the rating of casing or tubing. Hence, this study focuses on evaluating tubing's strength on the existing well whether the tubing is applicable for steam flooding or must be replaced. In this study, a tubing strength evaluation of well PDD-2 for steam flooding method will be discussed. Tubing strength evaluation consists of two stage. The first stage is evaluation due to burst, collapse, and tension loads and the other stage is evaluation due to thermal effects of injected steam. Well PDD-2 has K-55 tubing with 3.5 inch OD, burst rating of 7,947.5 psi, collapse rating of 7,052.9 psi, and tension rating of 160,262 Ibf. Based on the evaluation result, this existing K-55 tubing still be able to withstand the loads from burst, collapse, tension, and thermal effects. Hence, the reactivation of Well PDD-2 as steam injector well can be done without replacing or upgrading the tubing.